Zeitschrift für Kunstgeschichte (Deutscher Kunstverlag (DKV), 2018)
The »Zeitschrift für Kunstgeschichte« is one of the leading international journals for art historians around the world, publishing essays on all epochs, subjects and methodical approaches. Articles, reviewed by an independent body, are published in German, English, French or Italian.